Data Sheet 1_Transcriptome-wide prediction of heat-sensitive RNA structures in Zea mays.pdf - Mason W. Eisenhauer (22687085) (2025)
Introduction As global temperatures rise, understanding the potential effects on agriculture and food security is critical. Plant heat stress responses are finely controlled at transcriptional and post-transcriptional levels, with RNA secondary structure now recognized as an important regulator in this process. Methods To characterize and identify structure-function relationships in Zea mays, we applied the computational approach ScanFold to construct a transcriptome-wide database of RNA secondary structures and associated metrics. This database was analyzed at temperatures ranging from moderate 28°C to extreme 42°C. We performed an in-depth analysis of two heat shock factors, ZmHsf04 and ZmHsf17, as a case study for analyzing thermotolerance in maize. Results Using the database, we identified evolutionarily conserved RNA structures across the transcriptome that are sensitive to temperature-induced conformational switching. Our analysis of ZmHsf04 and ZmHsf17 yielded two key findings: many predicted structures are supported by significant sequence covariation, indicating evolutionary selection and likely functionality; and several structures of interest also exhibited extreme changes in conformation upon temperature increases. Discussion These identified structures in ZmHsf04 and ZmHsf17 may regulate gene expression through dynamic changes influencing processes like mRNA maturation, localization, expression, or alternative splicing, providing a rubric for understanding and approaching future studies of the transcriptome-wide dataset. The dataset and methodology presented here provide a rapid and robust approach to facilitate research into plant abiotic stress response, offering a crucial first step in understanding the role of RNA structure in Z. mays heat response.